Auf dem Weg zu einem fähigkeitsbasierten Digital Engineering Zielbild - Wyrwich, Fabian; Hovemann, Aschot; Dumitrescu, Roman (Tag des Systems Engineering 2025)

Design-for-decarbonization: a framework for decarbonizing cyber-physical production systems at the design stage - Schreiner, Nick; Cowen, Adam; Volling, Thomas; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: Cyber-physical production systems (CPPS) are responsible for a significant portion of manufacturers’ carbon emissions. Since 80% of product-related environmental impacts are determined at the design stage, there is a need for CPPS manufacturers to focus on decarbonization at the design stage. To date, there is a lack of design-for-decarbonization guidance for CPPS. This paper proposes a procedural framework for the effective selection of decarbonization measures for the design of CPPS. A Decarbonization Wheel is developed to establish a product-specific decarbonization strategy. This tool is linked to a catalogue of decarbonization measures. A measure prioritization logic provides a structure for systematizing selected measures. The framework is validated in the case of an intelligent industrial control valve.

Implementation of a web-based support platform for validation using system architecture in the B2B sector - Humpert, Lynn; Graunke, Jannis; Lewandowski, Lena; Schierbaum, Anja; Dumitrescu, Roman (2025 IEEE International Conference on Recent Advances in Systems Science and Engineering (RASSE))

Product Management: Tasks, Roles, and the Importance of Data - Grigoryan, Khoren; Martin, Lucas; Lamarz, Jessica; Fichtler, Timm; Hohn, Bennett; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Industry Perspectives on the Digital Product Passport: A Guide to Sustainable Value Chains From an Engineering Perspective - Trienens, Malte; Schreiner, Nick; Hovemann, Aschot; Dumitrescu, Roman (2025 IEEE European Technology and Engineering Management Summit (E-TEMS))

Product Decarbonization From an Engineering Perspective: Drawing Insights From Industry - Schreiner, Nick; Trienens, Malte; Kürpick, Christian; Asmar, Laban; Dumitrescu, Roman (2025 IEEE European Technology and Engineering Management Summit (E-TEMS))

Seeing the Signs – Supporting School Dog Welfare in England, Germany, the Netherlands and Wales with an Evidence-Based, Teacher-Friendly Dog Ethogram - Mombeck, Mona Maria; Grigg, R.; Lewis, H.; Oostendorp-Godfrey, J.; Pierard, M.; Van der Steen, S.

The Significance of Animal-Assisted Interventions for Children: Development, Implementation and Evaluation of a Canine-Assisted Programme to Support Resilience Development - Mombeck, Mona Maria; Caruso , Carina

Children’s Perception of Human and Non-Human Animals: A Pilot Study on the Development of Speciesist Attitudes - Wolf, J.; Mombeck, Mona Maria

Depict, Protect, Connect: A Scientific-Artistic Perspective on Humans and Non-Human Animals - Mombeck, Mona Maria

Bipartite entanglement extracted from multimode squeezed light generated in lossy waveguides - Kopylov, Denis; Meier, Torsten; Sharapova, Polina R. (APL Quantum)
Entangled two-mode Gaussian states constitute an important building block for continuous variable quantum computing and communication protocols. In this work, we theoretically study two-mode bipartite states, which are extracted from multimode light generated via type-II parametric downconversion (PDC) in lossy waveguides. For these states, we demonstrate that the squeezing quantifies entanglement and we construct a measurement basis, which results in the maximal bipartite entanglement. We illustrate our findings by numerically solving the spatial master equation for PDC in a Markovian environment. The optimal measurement modes are compared with two widely used broadband bases: the Mercer–Wolf basis (the first-order coherence basis) and the Williamson–Euler basis.

How Much to Pay for Tax Certainty? The Role of Advance Tax Rulings for Risky Investment under Loss Offset and Tax Uncertainty - Chen, An; Hieber, Peter; Sureth-Sloane, Caren
This study examines the impact of tax certainty through advance tax rulings (ATRs) on firms' risky investments under cash flow and tax uncertainty. Both firms and governments have expressed growing concern about increasing tax uncertainty, due to frequent tax reforms and the difficulty in applying ambiguous tax laws and anticipating audit outcomes. One remedy is the provision of ATRs, which offer upfront clarification of tax issues to reduce tax uncertainty and increase risk-taking. We analyze how these uncertainties, along with different tax rates, loss offset provisions, and ATR fees affect investment strategies. Our results suggest, first, that ATRs encourage riskier investments, particularly in tax regimes with generous loss offsets. We identify optimal ranges of ATR fees that benefit firms and tax authorities. Second, we show that it may be beneficial to design ATRs with a low or negative fee. Third, our study reveals a U-shaped relationship between firms' risk aversion and their willingness to pay for tax certainty, with willingness being higher for firms at low or high levels of risk aversion. In contrast, moderately risk-averse firms are only willing to accept low fees. Overall, our results highlight the importance of low-cost tax certainty combined with generous loss offset provisions to encourage risky investments.

Civic Statistical Literacy: Konzept und praxisnahe Umsetzung am Beispiel des Klimawandels - Biehler, Rolf; Engel, Joachim; Frischemeier, Daniel; Podworny, Susanne (mathematica didactica)

Development of an Effector-Specific Stop Signal Task with Higher Complexity: A Proof-of-Concept Study - Piskin, Daghan Yüksel; Gokeler, Alli; Chen, Yin-Hsuan; Baumeister, Jochen (Journal of Motor Behavior)

Exergaming Rejuvenates Resting-State Brain Complexity and Modulates Adaptability During Gameplay in Older Adults: An EEG Multiscale Entropy Study - Piskin, Daghan Yüksel; Müller, Helen Martha; Nina Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen

Skilled passing in football may regress following an anterior cruciate ligament injury as a result of cortical changes: preliminary EEG evidence - Piskin, Daghan Yüksel; Cobani, Gjergji; Lehmann, Tim; Büchel, Daniel; Baumeister, Jochen

Describing the nub in maximal Kac-Moody groups - Bischof, Sebastian; Marquis, Timothée
Let $G$ be a totally disconnected locally compact (tdlc) group. The contraction group $con(g)$ of an element $g\in G$ is the set of all $h\in G$ such that $g^n h g^{-n} → 1_G$ as $n → ∞$. The nub of $g$ can then be characterized as the intersection $nub(g)$ of the closures of $con(g)$ and $con(g^{-1})$. Contraction groups and nubs provide important tools in the study of the structure of tdlc groups, as already evidenced in the work of G. Willis. It is known that $nub(g) = \{1\}$ if and only if $con(g)$ is closed. In general, contraction groups are not closed and computing the nub is typically a challenging problem. Maximal Kac-Moody groups over finite fields form a prominent family of non-discrete compactly generated simple tdlc groups. In this paper we give a complete description of the nub of any element in these groups.

On flat groups in affine buildings - Bischof, Sebastian
In this article we work out the details of flat groups of the automorphism group of locally finite Bruhat-Tits buildings.

Mündliche Prüfungen im Mathematikunterricht – welche Arten des Wissens werden abgefragt? - Hellmund, Johannes (Beiträge zum Mathematikunterricht 2025)
Prüfungen sind ein wesentlicher Bestandteil des Mathematikunterrichts. Mündliche Prüfungsformate sind insbesondere in Abschlussprüfungen üblich, wurden aber bislang kaum untersucht. Dieses Projekt widmet sich dem Vorkommen und der Bedeutung verschiedener Wissensarten in mündlichen Prüfungen. Dazu soll auf Grundlage videografierter Prüfungsgespräche eine Taxonomie für abgefragte Wissensarten entwickelt werden. Der Vortrag präsentiert die Konzeption sowie erste Ergebnisse einer Vorstudie, die als Basis für eine vertiefte Analyse realer Prüfungen dient.

Tree-Based OWL Class Expression Learner over Large Graphs - Demir, Caglar; Yekini, Moshood Olawale; Röder, Michael; Mahmood, Yasir; Ngonga Ngomo, Axel-Cyrille (Lecture Notes in Computer Science)